(untitled) (Annals of Medical Research, 2023)
Aim: The aim of the study was to evaluate the effectiveness of plasmapheresis therapy in patients with snakebite who were admitted to intensive care unit in the setting of tertiary referral hospital. Materials and Methods: The retrospective study involved 114 adult patients with snakebite who were admitted to a referral hospital’s intensive care unit between January 2012 and December 2022. The patients were divided into four groups according to the treatments. Group AV performed antivenom (Group AV) alone. Group PP performed plasmapheresis alone. Group AV+PP performed antivenom and plasmapheresis. Group GST performed only general supportive therapy. Results: Fifty two of 114 were included in Group GST, 31 in Group AV, 18 in Group PP and 13 in Group AV+PP. APACHE score, SOFA score, GCS, stage of the bite, length of stay in the intensive care unit, acute kidney injury, and hematological disorders were higher while the platelet count at admission was lower in Group PP and Group AV+PP compared to Group AV and Group GST (p< 0.05). Conclusion: Antivenom and plasmapheresis are not alternatives to each other, antivenom should be performed to patients according to the severity of the bite, and plasmapheresis should be performed without delay in those with severe hematological effects.